Pre-service teachers’ learning styles and preferences towards instructional technology activities and collaborative works - Yusop, F.D.; Sumari, M. (Sakarya University, 2015)
The main purpose of this exploratory study was to investigate pre-service teachers’ learning styles and their preferences with respect to 15 technology-based instructional activities and collaborative work tasks. Felder and Silverman’s online Index of Learning Style (ILS) and a questionnaire were used to measure students’ learning styles and preferences. Respondents were 53 third year pre-service teachers in the Early Childhood Education program and the Islamic Studies program at a Malaysian public university. Data analyses involved both descriptive and inferential statistics to further understand the learning style patterns of pre-service teachers. Findings revealed that pre-service teachers in this program tended to be reflective in the way they process information, sensitive in the way they perceive information, visual in the way they receive information, and sequential in the way they understand information. Although no significant correlation was found between students’ learning styles and preferences towards collaborative and group work activities, interesting trends were observed in this study; active, intuitive, and global learners tended to dislike collaborative and group work activities when compared to reflective, sensing, and sequential learners. The findings of this study are important in assisting instructional technology instructors and higher education faculty in general in designing effective training programs for pre-service teachers particularly in relation to improve their technological skills.